PERLINDUNGAN HUKUM TERHADAP KORBAN ANAK TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA: OKTIR NEBI, S.H., M.H. - Oktir Nebi (JURNAL ADMINISTRASI NUSANTARA, 2020)
The results of the study show that issues relating to the regulation of legal protection for child victims of domestic violence, not all the rights of victims are clearly regulated, legal protection for child victims of domestic violence that is not clearly regulated. Therefore, criminal law reforms must be carried out on the provisions of legal protection for child victims of domestic violence that are regulated in the legislation, especially against child victims of domestic violence so that there is a legal umbrella that can guarantee the emergence of a sense of justice and certainty in the community.